Regulación de la vía de tnf-a/nfkb por acción de la glicina en adipocitos - Contreras Núñez, Erika (Universidad Autónoma Metropolitana, 2018)
Introduction: Glycine, an amino acid non-essential and simple structure consisting of a hydrogen as a side chain (Lynch, 2004); it has shown to be protective against cell injury, providing cytoprotection (Zhong et al., 2003). Likewise, it partnered with the blocking of the systemic inflammatory process that originates in a variety of pathological states. These processes involve powerful inflammatory mediators, such as cytokines, which play an important role in the progressive inflammatory response (Matilla et al., 2002; Zhong et al., 2003). The effects of glycine are regulated by a specific receptor (GlyR), which is anchored to the plasma membrane and associated with Cl- channels. When there is the union of glycine to your receiver, it exerts its inhibitory action (Chatterton et al., 2002; Laube et al., 2002); such action of the glycine can be selectively blocked by strychnine (Sakata et al., 2001). So far investigations on the effects of glycine in vitro and in vivo studies have shown that decreases the expression and secretion of proinflammatory cytokines and increases the anti-inflammatory (Alarcón-Aguilar et al., 2008; Almanza-Perez et al., 2010; Garcia - Macedo et al., 2008). Effects that have been associated with the participation of the transcription factor NF-kB (nuclear factor kappa B), which promotes transcription of genes encoding proinflammatory cytokines and chemokines, which have as main function to recruit macrophages polymorphonuclear site of tissue damage, to kill the invader by phagocytosis or trying to regulate the inflammatory process with the synthesis of anti-inflammatory cytokines (Hayden and Ghosh, 2004). It has been shown that pretreatment with glycine suppresses the activation of this vii transcription factor as well as the activity of its inhibitor and the complex IKK-a resulting in a decrease in the synthesis of proinflammatory cytokines and an improvement in the profile inflammatory (Blancas-Flores et al., 2012; ContrerasNuñez., 2013). This research intends to continue with the elucidation of the mechanism of action of glycine in adipocytes explaining his participation in the inflammatory process. General objective: determine if the anti-inflammatory effect of glycine occurs by inhibition of IKK-a/b complex on via TNF-a/NF-kB by binding to a specific receiver. Material and methods: We used the cell line 3T3-L1; the cells were incubated with TNF - (5 ng/mL) for 30 min (positive control), BAY (10 µM, an inhibitor of NF-kB) during 30 min (negative control), and pretreatment with glycine (10 mM) to 15, 30, 45, 60, 120 and 240 min. He was the extraction of nuclear and cytoplasmic protein for its quantification. Applied technique of the Western Blot for detection of protein kinases (IKK-a/b). The activation of NF-kB as well as the secretion of cytokines (IL-6, TNF-a and adiponectin) was measured by ELISA method. He was the extraction of mRNA and applied the technique of RT-PCR for the quantification of cytokines (IL-6, TNF-a and adiponectin) and the expression of glycine receptor. The [Ca2+]i and determined the location of the receiver of glycine in the membrane by confocal microscopy. In trials to determine a possible presence of receptors for glycine (glycine receptor antagonist) strychnine was used by the ELISA method in which measured the activation of NF-kB. The data were analyzed using an analysis of variance followed by complementary Tukey-Kramer test, with a significance level of 95%. Results: The results showed that glycine decreased the presence of IKK-a at 30, 60 and 120 min, as well as the p-IKK-a (Thr 23) to 15, 60, 120, 240 min. However, the complex IKK-a/b decreased its presence at 15 min and showed a significant increase at 240 min relative to the positive control TNF-a, there was also a decrease in the content of p-IKK-a/b (Ser176/177) at 30, 60, 120 and 240 min. This coincided with a decrease in phosphorylation of p65 NF-kB (pS536). Effect that caused a decrease in the expression and secretion of IL-6 and TNF-a. Expression and secretion of adiponectin were increased. It also showed that glycine generates a decrease in the [Ca+2]i increasing the expression of mRNA of receptor (GlyR) glycine, as well as its location in the Adipocyte plasma membrane. Conclusión: IKK-a/b is regulated by the action of glycine, interfering in their activity and, consequently, by suppressing the activation of NF-kB, action associated with a specific receptor that causes a hyperpolarization in the plasma membrane of the adipocyte, generating blockade of voltage-dependent channels, as of Ca+2, regulating the expression and secretion of proinflammatory cytokines (IL-6, TNF-a) and increasing an anti-inflammatory cytokine (adiponectin) in 3T3-L1 adipocytes, contributing to the reduction of the inflammatory process at the systemic level.; Introducción: La glicina, un aminoácido no esencial y de estructura simple constituida por un hidrógeno como cadena lateral (Lynch, 2004); ha mostrado ser protector contra la lesión celular, proporcionando citoprotección (Zhong y col., 2003). Así mismo, se ha asociado con el bloqueo del proceso inflamatorio sistémico que se origina en una amplia variedad de estados patológicos. En estos procesos participan potentes mediadores inflamatorios, tales como las citocinas, las cuales desempeñan un importante papel en la respuesta inflamatoria progresiva (Matilla y col., 2002; Zhong y col., 2003). Los efectos de la glicina están regulados por un receptor (GlyR) específico que se encuentra anclado a la membrana plasmática y asociado a canales de Cl- . Cuando se presenta la unión de glicina a su receptor, éste ejerce su acción inhibidora (Chatterton y col., 2002; Laube y col., 2002); dicha acción de la glicina puede ser bloqueada selectivamente por estricnina (Sakata y col., 2001). Hasta el momento las investigaciones realizadas sobre los efectos de la glicina en estudios in vitro e in vivo han demostrado que disminuye la expresión y secreción de citocinas proinflamatorias y aumenta las antiinflamatorias (Alarcon-Aguilar y col., 2008; Almanza-Perez y col., 2010; Garcia-Macedo y col., 2008). Efectos que se han relacionado con la participación del factor de transcripción NF-kB (factor nuclear kappa B), el cual promueve la transcripción de genes que codifican para citocinas proinflamatorias y quimiocinas, las cuales tienen como función principal reclutar macrófagos polimorfonucleares al sitio del daño tisular, para eliminar al invasor por fagocitosis o tratar de regular el proceso inflamatorio con la síntesis de citocinas iv antiinflamatorias (Hayden and Ghosh, 2004). Se ha demostrado que el pretratamiento con glicina suprime la activación de este factor de transcripción así como la actividad de su inhibidor y del complejo IKK-a/b, dando como resultado una disminución en la síntesis de citocinas proinflamatorias y una mejora en el perfil inflamatorio (Blancas-Flores y col., 2012; Contreras-Nuñez., 2013). La presente investigación pretende continuar con la elucidación del mecanismo de acción de la glicina en adipocitos que explique su participación en el proceso inflamatorio. Objetivo general: Determinar si el efecto antiinflamatorio de la glicina ocurre por la inhibición del complejo IKK-a/b sobre la vía TNF-a/NF-kB por unión a un receptor específico. Material y métodos: Se utilizó la línea celular 3T3-L1; las células fueron incubadas con TNF-a (5 ng/mL) durante 30 min (control positivo), BAY (10 µM, un inhibidor de NF-kB) durante 30 min (control negativo) y pretratamientos con glicina (10 mM) a los 15, 30, 45, 60, 120 y 240 min. Se realizó la extracción de proteína nuclear y citoplasmática para su cuantificación. Se aplicó la técnica del Western Blot para la detección de las proteínas cinasas (IKK-a/b). Por el método de ELISA se midió la activación de NF-kB así como la secreción de citocinas (IL-6, TNF-a y adiponectina). Se realizó la extracción de RNAm y se aplicó la técnica de RT-PCR para la cuantificación de citocinas (IL-6, TNF-a y adiponectina) y la expresión del receptor de glicina. Se determinó la [Ca2+]i y la localización del receptor de glicina en la membrana por medio de microscopia confocal. En los ensayos para determinar una posible presencia de los receptores para glicina fue utilizada la Estricnina v (antagonista del receptor de glicina) por el método de ELISA en el cual se midió la activación de NF-kB. Los datos se analizaron mediante un análisis de varianza seguido de la prueba complementaria de Tukey-Kramer, con un nivel de significancia del 95%. Resultados: Los resultados mostraron que la glicina disminuyó la presencia de IKKa a los 30, 60 y 120 min, así como en la p-IKK-a (Thr 23) a los 15, 60, 120, 240 min. Sin embargo, el complejo IKK-a/b disminuyó su presencia a los 15 min y se apreció un aumento significativo a los 240 min con respecto al control positivo TNF-a, así mismo se observó una disminución en el contenido de p-IKK-a/b (Ser176/177) a los 30, 60, 120 y 240 min. Esto coincidió con una disminución en la fosforilación de p65 NF-kB (pS536). Efecto que generó una disminución en la expresión y secreción de IL-6 y TNF-a. La expresión y secreción de adiponectina se incrementaron. También se mostró que glicina genera una disminución en las [Ca+2]i aumentando la expresión del RNAm del receptor de glicina (GlyR), así como su localización en la membrana plasmática del adipocito. Conclusión: IKK-a/b es regulada por la acción de la glicina, interfiriendo en su actividad y, en consecuencia, suprimiendo la activación de NF-kB, acción asociada a un receptor específico que provoca una hiperpolarización en la membrana plasmática del adipocito, generando bloqueo de los canales dependientes de voltaje, como los de Ca+2, regulando la expresión y secreción de citocinas proinflamatorias (IL-6, TNFa) y aumentando una citocina antiinflamatoria (adiponectina) en adipocitos 3T3-L1, contribuyendo a la reducción del proceso inflamatorio a nivel sistémico.